Caspase-11 Modulates Inflammation and Attenuates Toxoplasma gondii Pathogenesis. (9th June 2016) - Coutermarsh-Ott, Sheryl L.; Doran, John T.; Campbell, Caroline; Williams, Tere M.; Lindsay, David S.; Allen, Irving C.
Abstract : Toxoplasma gondii is an obligate intracellular parasite that is the etiologic agent responsible for toxoplasmosis. Infection with T. gondii results in activation of nucleotide binding domain and leucine rich repeat containing receptors (NLRs). NLR activation leads to inflammasome formation, the activation of caspase-1, and the subsequent cleavage of IL-1 β and IL-18. Recently, a noncanonical inflammasome has been characterized which functions through caspase-11 and appears to augment many biological functions previously considered to be dependent upon the canonical inflammasome. To better elucidate the function of this noncanonical inflammasome in toxoplasmosis, we utilized Asc −/− and Casp11 −/− mice and infected these animals with T. gondii . Our data indicates that caspase-11 modulates the innate immune response to T. gondii through a mechanism which is distinct from that currently described for the canonical inflammasome. Asc −/− mice demonstrated increased disease pathogenesis during the acute phase of T. gondii infection, whereas Casp11 −/− mice demonstrated significantly attenuated disease pathogenesis and reduced inflammation. This attenuated host response was associated with reduced local and systemic cytokine production, including diminished IL-1 β . During the chronic phase of infection, caspase-11 deficiency resulted in increased neuroinflammation and tissue cyst burden in the brain. Together, our data suggest that caspase-11 functions to protect the host by enhancing inflammation during the early phase of infection in an effort to minimize disease pathogenesis during later stages of toxoplasmosis.